2009
DOI: 10.1038/nature08632
|View full text |Cite|
|
Sign up to set email alerts
|

Ecoenzymatic stoichiometry of microbial organic nutrient acquisition in soil and sediment

Abstract: Biota can be described in terms of elemental composition, expressed as an atomic ratio of carbon:nitrogen:phosphorus (refs 1-3). The elemental stoichiometry of microoorganisms is fundamental for understanding the production dynamics and biogeochemical cycles of ecosystems because microbial biomass is the trophic base of detrital food webs. Here we show that heterotrophic microbial communities of diverse composition from terrestrial soils and freshwater sediments share a common functional stoichiometry in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
814
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,187 publications
(867 citation statements)
references
References 27 publications
41
814
12
Order By: Relevance
“…C, N, P) and the recalcitrance, or the resistance to decomposition, of the molecules comprising the litter. Decomposition is generally favored by relatively low litter C:N ratios (Cleveland and Liptzin, 2007), which presumably helps to maintain the low C:N ratio of microbial cells (Sinsabaugh et al, 2009;Manzoni et al, 2010), yet, there is increasing evidence that additional aspects of quality beyond basic stoichiometry also can play a role determining decomposition rates. Koide and Malcolm (2009) tested the role of C and N concentrations on the decomposition rate of EM fungal necromass in a litterbag study and found that initial N concentration was a good predictor of the decomposition rate of these tissues.…”
Section: Necromass Stoichiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…C, N, P) and the recalcitrance, or the resistance to decomposition, of the molecules comprising the litter. Decomposition is generally favored by relatively low litter C:N ratios (Cleveland and Liptzin, 2007), which presumably helps to maintain the low C:N ratio of microbial cells (Sinsabaugh et al, 2009;Manzoni et al, 2010), yet, there is increasing evidence that additional aspects of quality beyond basic stoichiometry also can play a role determining decomposition rates. Koide and Malcolm (2009) tested the role of C and N concentrations on the decomposition rate of EM fungal necromass in a litterbag study and found that initial N concentration was a good predictor of the decomposition rate of these tissues.…”
Section: Necromass Stoichiometrymentioning
confidence: 99%
“…Relatively labile compounds can persist in SOM for long periods as a consequence of physical protection either through soil aggregation or sorption (Nelson et al, 1979;Six et al, 2006;Grandy and Robertson, 2007;Grandy and Neff, 2008). Fungal hyphae have intimate physical and chemical interactions with soil structures, which can lead to stabilization and protection of organic compounds in soils (Tisdall, 1994;Rillig et al, 2015).…”
Section: Physical and Spatial Protectionmentioning
confidence: 99%
“…Microbial growth requires a stoichiometric balance between carbon and other elements (especially nitrogen and phosphorus; Frost et al 2006;Nordgren et al 1988;Sinsabaugh et al 2009). If the availability of other nutrients is below the stoichiometric requirements, there is a risk that excess carbon will be respired and converted into CO 2 (or excreted in the form of organic compounds) rather than being used for biosynthesis, leading to reduced CUE (Ågren and Bosatta 1987;Manzoni and Porporato 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Soil enzyme activities integrate information about microbial status and soil physicochemical conditions (Aon and Colaneri, 2001;Sinsabaugh et al, 2010), and are indicators of the functioning of soil ecosystems (Ciarkowska et al, 2014). They have been similarly used in studies on the effectiveness of reclaimed treatments on soil quality (Li et al, 2012;Schimann et al, 2012;Finkenbein et al, 2013;Ciarkowska et al, 2014).…”
Section: Introductionmentioning
confidence: 99%